Gonta I. A. The translation of compound and compound derivatives in Oskar Wild «The picture of Dorian Gray» - Gonta I. A. (Philological Treatises, 2020)
The article deals with analyzing compound words denoting colours in the work by Oscar Wilde „The Picture of Dorian Gray‟ – their morphological structure, cultural and stylistic functions, the ways of their translation in the Ukrainian language in the interpretation of the translator.